Cywilizacja i kanonizacja prawa o aktach stanu cywilnego - Szadok-Bratuń, Aleksandra (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
In the Polish legal doctrine the dispute over the place of two normative acts - the Family and Care Code and the law on Civil Registry Records acts - in the civil law system returns from time to time. One of the advantages of this dispute is the possibility of showing the interference of public and private law. The introduction to the domestic jurisprudence the canonical form of civil marriage resulted in the incorporation of certain elements of the canon law into it. Hence, it is possible to speak of the dualistic construction of permeation of legal regimes in the fora of state law and canon law. This specific frontier is reflected by the subject specificity of the law on civil status records characterized by two-staged, dual merging of different legal orders. At the first stage, in the area of the state legal system, there is dualism: administrative law (public) ‒ family law (private). At the other, in the area of interference of the Polish and religious legal order, there is dualism: state law ‒ canon law. The first-degree dualism was conventionally defined as the „civilization” of the law on civil registry records acts and the second-degree dualism ‒ the „canonization” of the civil-law code.
Keywords: kodeks rodzinny i opiekuńczy; prawo o aktach stanu cywilnego; prawo kanoniczne; dualizm prawa; kanoniczna forma zawarcia małżeństwa cywilnego; przenikanie porządków prawnych